PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA PEMBELI PRODUK DI BUTIK FELUCY SEMARANG) - Ika Septiani Rahayu, 12.05.51.0129 (Students Journal of Economic and Management, 2016)
Development of fashion and fashion in Indonesia is quite rapidly with the support of creativity and innovations of young designers. As time went boutiques began to appear, the boutique offers a product that is intended for women and more precisely young people today who want to look beautiful and more fashionable to follow the existing model. This study aimed to analyze the influence of Product Quality, Perceived Price, and Promotion of the buying decision. The sample used in this study were 100 respondents to the sampling technique is purposive sampling method, the sample carefully selected to take the research object selective and has specific characteristics. The data used are primary data, data analysis used include validity, reliability, multiple linear regression, determination coefficient and hypothesis test which includes the F test and t test. Based on data analysis and hypothesis testing showed that partial variable product quality and significant positive influence on purchasing decisions. Price perception variable positive and significant impact on purchasing decisions.Variable promotions positive and significant impact on purchasing decisions. Variable product quality, perceived price and promotion together positive and significant impact on purchasing decisions. The test results of determination is known variable product quality, perceived price and promotional able to explain the variation of 70.8% on purchasing decisions while the remaining 29.2% is influenced by other variables not analyzed in this study. Keywords: Product Quality, Perceived Price, Promotion and Purchase Decision